Nickel toxicity in common bean plants and effects on soil microbiota - Berton, Ronaldo Severiano; Moreno Pires, Adriana Marlene Moreno; Andrade, Sara Adrián López de; Abreu, Cleide Aparecida de; Ambrosano, Edmilson José; Silveira, Adriana Parada Dias da (Pesquisa Agropecuaria Brasileira, 2006)
The aim of this work was to evaluate the effect of Ni addition (0, 2.3, 10.5, 47 and 210 mg kg-1), in the presence and absence of lime, on: common beans development, Ni phytoavailability, and soil biological characteristics. A greenhouse experiment was conducted using a sample of a Rhodic Hapludox. Rate of 210 mg kg-1 of Ni caused plant death in both the absence and the presence of lime. Grain yield of common beans was higher in treatments with lime addition. However, grain Ni concentration increased with Ni addition, exceeding the maximum admissible value, of 5 mg kg-1 (fresh weight), already at rate of 2.3 mg kg-1. Lime addition was not enough to reduce grain Ni concentrations to permissible levels for consumption. The addition of high concentrations of Ni decreased soil microbial biomass, and this reduction was accompanied by an increase in the metabolic quocient. The qCO2 was an adequate indicator of the stress level caused by Ni addition on soil microbial community.